Analisis Pengaruh Aksesibilitas Ruas Jalan Yos Sudarso, Jalan Jendral Sudirman, dan Jalan Mulawarman Terhadap Nilai Jual Lahan di Kota Tarakan - Achmad Zultan M; Eko Sariyanto (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2017)
One of the steps that taken by the Government of Tarakan City in supporting the development of the city is by the way of developing transportation of infrastructure in the form of a road network that aims to provide accessibility, for making it easier for people to do the movement. This study aims to find out the sale value of land for connection with the accessibility of the road and to know the accessibility factor of the road that has the most influence on the sale value of land in the city of Tarakan. Sampling was conducted on three streets namely, Yos Sudarso road, Mulawarman road, and Sudirman road as the location of this research. From the data that obtained were analyzed by using statistical analysis that using by multiple regression. For this analysis shows that the results of 70.6% of the variable sale value of land can be explained by the intensity variable of city transportation. The most influential accessibility factor of the sale value of land is the intensity of city transportation, which every addition of public transportation 8 vehicle / hour will increase the sale value of land amounted to Rp. 394,527.40 per m².